Natural Products for Cancer Prevention and Therapy - Anupam Bishayee (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. [This Special Issue book, "Natural Products for Cancer Prevention and Therapy", is based on recent advances in natural products for cancer prevention and therapy. For this purpose, the authors of this book have been organizing a biennial international conference series. The first meeting (First International Conference on Natural Products for Cancer Prevention and Therapy) was held in Istanbul between 31 August and 2 September 2015, with the support and contribution of many valuable researchers in this field. The abstracts of the first conference were published in the Anticancer Drugs journal as a supplement. The second meeting, namely The Second International Conference on Natural Products for Cancer Prevention and Therapy, was held at Erciyes University, Kayseri, Turkey, between 8 and 11 November 2017. The abstracts of all of the presentations from the second meeting were published in the Special Issue of Proceedings by the MDPI publishing group. Furthermore, the conference report and the selected full-length papers based on the presentations at the meeting, as well as other papers based on natural products for cancer prevention and therapy, were published as a Special Issue of the Nutrients journal from MDPI. This Special Issue has contributions from various participants of the aforementioned conference, as well as other cancer and natural product researchers. These contributions include original research papers, authoritative and up-to-date reviews, and commentaries on the following topics and areas: •Natural products for the prevention and therapy of oncologic diseases •Mechanism of natural agents for anticancer and cancer preventive effects •In vitro, in vivo, and clinical studies related to natural agents and cancer • Combinatorial effects of phytochemicals and cancer chemotherapeutic drugs •Challenges and innovative approaches for anticancer drug development based on natural products •Emerging studies on anticancer phytochemicals]